Testing urban drivers of riparian woody vegetation composition in a precipitation‐limited system. (28th October 2019) - Solins, Joanna P.; Cadenasso, Mary L.
Abstract: In precipitation‐limited regions, where water availability is a key driver of vegetation patterns, altered hydrology in urban areas may have a particularly strong effect on riparian plant communities. Urban water inputs can create perennial flows in formerly intermittent streams, potentially providing a water subsidy to riparian plants during dry seasons. However, during rainy seasons, increased storm flow magnitudes in urban areas can cause stream channel incision and associated lowered water tables. Channel incision may reduce riparian soil moisture throughout the year and limit the effect of dry‐season stream flow. We investigated whether channel incision and dry‐season stream flow were related to the composition of riparian vegetation communities along small streams in Sacramento, California, United States, and whether these two factors interacted. Sacramento has a Mediterranean climate with a long summer dry season. We sampled the riparian woody plant community along 66 stream reaches that created a gradient of channel incision severity across sites with and without dry‐season flow. The riparian vegetation community was more strongly related to channel incision than dry‐season flow. The two factors did interact in relation to the overall community composition based on multivariate analyses, but we did not detect interactions in univariate generalized linear mixed models predicting specific components of the woody vegetation community, with the exception of large native oak trees. We found that wetland‐associated species and non‐native species both became less prevalent with increasing channel incision. Conversely, native upland oak trees became more prevalent with increasing incision, although large oak trees only showed this pattern along flowing streams. Wetland‐associated seedlings were almost exclusively found along flowing streams. Synthesis . Our findings suggest that channel incision is a key driver of riparian woody vegetation composition. Although the effects of dry‐season flow were less pronounced, urban water subsidies may be essential for the establishment of wetland‐associated trees along historically intermittent streams. Varied hydrological conditions in precipitation‐limited cities are associated with divergent assemblages of woody species in riparian zones. Abstract : Our results suggest that changes in hydrology can strongly influence riparian woody vegetation communities in a precipitation‐limited urban system. Channel incision appears to be a key driver of community composition, while increased dry‐season flow due to urban water inputs may be essential for the establishment of wetland‐associated trees along historically intermittent streams.